Tahfidz Alquran Learning Model in Pesantren: an Example from West Java, Indonesia - Badruzzaman, M. Yunus; Imelda Helsyi; Eni Zulaiha (Indonesian Journal of Islamic Studies, 2018)
This article focuses on the discussion of effective and efficient tahfidz Al-Qur'an learning that has been developed by Podok Tahfidz Hikamus Salafiyyah Cirebon and the pesantren Al-Khoeriyyah-Sukabumi) which has demonstrated its success in giving birth to Quranic hafidul and mufassir, who are ready to compete in various musabaqoh events. local to the international level. The object is to look for models of tahfidz al-Quran distribution that are applied in these two pesantren. Through a study of qualitative descriptive methods with instruments that collect data in the form of observation, documentation study and interview writing, this shows that the implementation of tahfidz Alquran learning in Al-Khairiyyah and pesantren MQHS when viewed from the learning elements has been well established, starting from planning, implementation, and evaluation. ; The interaction pattern built by the pesantren community in creating an academic culture is the existence of a peer tutor program, maximum supervision, and service, building a constructive environment; Appreciation of pesantren for students who excel in the form of full scholarships (living and school fees), given jobs and mated and financed by pesantren; Supporting resources that greatly influence the success of pesantren are highly qualified human resources (all hafidz who have already achieved), adequate funding so that all santri are free.